Insulin and IGF1 receptors are essential for XX and XY gonadal differentiation and adrenal development in mice. - Jean-Luc Pitetti; Pierre Calvel; Yannick Romero; Béatrice Conne; Vy Truong; Marilena D Papaioannou; Olivier Schaad; Mylène Docquier; Pedro Luis Herrera; Dagmar Wilhelm; Serge Nef (PLoS Genetics)
Mouse sex determination provides an attractive model to study how regulatory genetic networks and signaling pathways control cell specification and cell fate decisions. This study characterizes in detail the essential role played by the insulin receptor (INSR) and the IGF type I receptor (IGF1R) in adrenogenital development and primary sex determination. Constitutive ablation of insulin/IGF signaling pathway led to reduced proliferation rate of somatic progenitor cells in both XX and XY gonads prior to sex determination together with the downregulation of hundreds of genes associated with the adrenal, testicular, and ovarian genetic programs. These findings indicate that prior to sex determination somatic progenitors in Insr;Igf1r mutant gonads are not lineage primed and thus incapable of upregulating/repressing the male and female genetic programs required for cell fate restriction. In consequence, embryos lacking functional insulin/IGF signaling exhibit (i) complete agenesis of the adrenal cortex, (ii) embryonic XY gonadal sex reversal, with a delay of Sry upregulation and the subsequent failure of the testicular genetic program, and (iii) a delay in ovarian differentiation so that Insr;Igf1r mutant gonads, irrespective of genetic sex, remained in an extended undifferentiated state, before the ovarian differentiation program ultimately is initiated at around E16.5.